Vanishing Boycott Impetus: Why and How Consumer Participation in a Boycott Decreases Over Time - Wassili Lasarov; Stefan Hoffmann; Ulrich Orth (Journal of Business Ethics, 2021)
Media reports that a company behaves in a socially nonresponsible manner frequently result in consumer participation in a boycott. As time goes by, however, the number of consumers participating in the boycott starts dwindling. Yet, little is known on why individual participation in a boycott declines and what type of consumer is more likely to stop boycotting earlier rather than later. Integrating research on drivers of individual boycott participation with multi-stage models and the hot/cool cognition system, suggests a "heat-up" phase in which boycott participation is fueled by expressive drivers, and a "cool-down" phase in which instrumental drivers become more influential. Using a diverse set of real contexts, four empirical studies provide evidence supporting a set of hypotheses on promotors and inhibitors of boycott participation over time. Study 1 provides initial evidence for the influence of expressive and instrumental drivers in a food services context. Extending the context to video streaming services, e-tailing, and peer-to-peer ridesharing, Study 2, Study 3, and Study 4 show that the reasons consumers stop/continue boycotting vary systematically across four distinct groups. Taken together, the findings help activists sustain boycott momentum and assist firms in dealing more effectively with boycotts.
Keywords: 300; Boycott; Dynamics; Perceived egregiousness; Hot/cool cognition